Abordagem terapêutica com um lisado bacteriano (om-85) frente a infecção pelo virus sars-cov-2 : um estudo experimental ex vivo - Cassão, Gisele (2022)
Introduction: The COVID-19 pandemic, caused by the SARS-CoV-2 virus, affects many people around the world. Even with the development of vaccines, there is an urgent need to develop effective therapeutic approaches to combat and prevent this viral infection. OM-85 is an immunostimulating bacterial lysate capable of modulating the antiviral response, already used to prevent recurrent respiratory infections acute otitis media, pneumonia, rhinitis, pharyngotonsillitis, asthma, chronic obstructive pulmonary disease). Objective: To understand whether bacterial lysate (OM-85) is able to activate molecular antiviral mechanisms in SARS-CoV-2 infected cells. Methods: This is an ex vivo experimental study. Epithelial cells from nasal lavage of patients with COVID-19, diagnosed by RT-PCR, with up to 48 hours of hospital admission and within three weeks of the onset of symptoms, were cultured for 24 hours in the presence of OM-85 (10 μg /ml) and 2.5 ng/ml of IFNβ. RNA from cells was extracted and performed by RT-PCR, analysis of the relative expression of the SARS-CoV-2 N1 gene, the ACE2 virus receptor gene and the genes related to the antiviral response, ISG15, MAVS, MDA5, OASL, IRF3, RIG-I, IFNλ and with inflammatory response, IL-6, IL-8, mTOR, TRL2, TLSP, IL1B. Cell supernatant was collected for cytokine analysis by ELISA. In addition, A549WT and Calu-3 cell lines were cultured, infected with SARS-CoV-2 for one hour and treated with OM-85 for 24 hours. Results: Treatment with OM-85 reduced the viral gene expression of SARS-Cov-2 and increased the expression of the RIG-I molecule. Analyzes on the expression of IFNB, ISG15, IL-6, MDA5, OASL, IL1B had no statistical significance in their expression when comparing the group of untreated cells with the treated group. The gene expression of IL-8, MAVS, IRF3, mTOR, IFNλ, TRL2, TLSP and ACE2 was not detected. When analyzing the proteins IFNB, IL-6, IL-8, IL-10 and TNFα by ELISA test, there was no relevant difference between the control group and the treated group. This was repeated when we analyzed the correlations of these same proteins, as well as with the other cytokines, with the expression of SARS-CoV-2. As for the in vitro experiment, the analysis of the gene expression of the virus showed a tendency to reduce this expression in A549WT cells when treated with OM-85; which was not observed in the Calu-3 lineage. Conclusion: Our data complement previous studies that show a protective effect of OM-85 against SARS-CoV-2 infection in mice. Clinical trials are needed to confirm a possible therapeutic or prophylactic use against coronavirus infection.